Ultrasonic spray coating polymer and small molecular organic film for organic light-emitting devices - Liu, Shihao (Sci Rep, 2016)
Ultrasonic spray coating process (USCP) with high material -utilization, low manufacture costs and compatibility to streamline production has been attractive in researches on photoelectric devices. However, surface tension exists in the solvent is still a huge obstacle to realize smooth organic film for organic light emitting devices (OLEDs) by USCP. Here, high quality polymer anode buffer layer and small molecular emitting layer are successfully realized through USCP by introducing extra-low surface tension diluent and surface tension control method. The introduction of low surface tension methyl alcohol is beneficial to the formation of poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) films and brings obvious phase separation and improved conductivity to PEDOT:PSS film. Besides, a surface tension control method, in which new stable tension equilibrium is built at the border of wetting layer, is proposed to eliminate the effect of surface tension during the solvent evaporation stage of ultrasonic spray coating the film consists of 9,9-Spirobifluoren-2-yl-diphenyl-phosphine oxide doped with 10 wt% tris [2-(p -tolyl) pyridine] iridium (III). A smooth and homogenous small molecular emitting layer without wrinkles is successfully realized. The effectiveness of the ultrasonic spray coating polymer anode buffer layer and small molecular emitting layer are also proved by introducing them in OLEDs.